1992
DOI: 10.1002/food.19920360307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat, processing time and pH on the microflora, aflatoxin content and storability of “wara”, a soft, white cheese

Abstract: SummaryEmploying crude coagulants from sodom apple Calotropis procera, processing conditions of 65 -85 "C for 40-65 min and reduced pH, reductions in microbial population were found in a locallyproduced soft, white cheese "wara". The finished product "wara" did not keep well under ambient conditions (RH 75 5%, temp. 26 _+ 2 "C). From some selected critical control points along the line of processing, Bacillus spp., coliforms, staphylococci and moulds Aspergillus and Mucor spp. were isolated. Aflatoxin B, (AFB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
2
13
2
Order By: Relevance
“…At this point, the populations of total aerobes, Enterobactericeae, psychrotrophs, and mold and yeast decreased to the undetectable level except for the total aerobic counts in the milk inoculated with 10 1 CFU ml À1 of L. monocytogenes which was approximately 1.30 Log 10 CFU ml À1 (Table 1). Adegoke et al (1992) observed a similar decrease in the population of total aerobes at the cooking point during wara manufacture. The inoculated L. monocytogenes was not found at the curdling point (Table 1) and throughout the 5 d storage period at 28 and 15 1C in this study (data not shown).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…At this point, the populations of total aerobes, Enterobactericeae, psychrotrophs, and mold and yeast decreased to the undetectable level except for the total aerobic counts in the milk inoculated with 10 1 CFU ml À1 of L. monocytogenes which was approximately 1.30 Log 10 CFU ml À1 (Table 1). Adegoke et al (1992) observed a similar decrease in the population of total aerobes at the cooking point during wara manufacture. The inoculated L. monocytogenes was not found at the curdling point (Table 1) and throughout the 5 d storage period at 28 and 15 1C in this study (data not shown).…”
Section: Resultssupporting
confidence: 62%
“…Other researchers have isolated Penicillium and Aspergillus spp. from wara in earlier studies (Adegoke et al, 1992). The results of this study suggest that without efficient preservation, the recommended holding time of wara cheese should be significantly shortened.…”
Section: Article In Pressmentioning
confidence: 80%
See 2 more Smart Citations
“…[5]. In many parts of tropical Africa, milk and milk products are scarce and unaffordable by the majority of the populace [6]. The high and unaffordable cost of milk in some developing countries like Nigeria has made it necessary to source less expensive plant products that could be used as substitutes for milk products or to augment the use of milk products for effectiveness in fighting protein malnutrition.…”
Section: Introductionmentioning
confidence: 99%